Enzymes of Trichoderma and other origin in biopreparation of cotton - Anita Losonczi; George Szakacs; Emilia Csiszar; Outi Kareela (浙江大学学报. 农业与生命科学版)
Preparation and bleaching are among the most energy and chemical intensive steps of the traditional cotton finishing. About 75% of the organic pollutants arising from textile finishing are derived from the preparation of cotton goods. Biopreparation may be a valuable and environmentally friendly alternative to harsh alkaline chemicals for preparing of cotton. Different enzymes i. e. cellulases, pectinases, lipases and proteases have been tested for biopreparation. Many papers have been published how enzymes effect on the properties of cotton fabrics in respect to their effectiveness to replace alkaline scouring and how enzymes modify the various cell wall components of cotton fibers. However, very few data have been reported on bleachability and dyeing behavior of the bioscoured fabrics.In this work an acidic cellulase (Celluclast 1.5 L, Trichoderma reesei origin), an acidic pectinase-hemicellulase (Viscozyme 120 L, Aspergillus aculeatus) and a cellulase-free xylanase (Pulpzyme HC, Bacillus sp.) enzymes were used for bioscouring of greige cotton fabric. Selected properties of the pretreated samples, which are important for effective dyeing, are characterized in detail. Effect of hydrogen peroxide bleaching, applied subsequent to the biopretreatment on the bleachability and dyeing properties of the samples is also elucidated. A reactive dye was used at four different concentrations to compare the dyeing behavior of biopretreated as well as biopretreated and subsequently bleached cotton fabrics with that of the alkaline scoured as well as alkaline scoured and bleached fabrics, respectively. Color evenness and uniformity, and wash fastness properties of the dyed samples are also determined[1].